Entre la progresión y la regresión : la configuración identitaria en los procesos de pérdida (2013)
ABSTRACT: It is approached the problem of identity configuration in the case of a subject who has experienced the loss of significant people. We recall the following theorist: Kenneth Gergen, for whom personal identity is a narration built into relationships with the others; Paul Ricoeur, who proposes a narrative identity; John Bowlby with his theory of attachment; and finally, Robert Neimeyer, who refers to psychotherapy in loss processes. As a conclusion, it is proposed that identity configuration in processes of loss can occur in two narrative ways, regressive or progressive; and some of the contributing factor to the progressive identity orientation could be the set of relations, the attachment, as well as stories and rituals.